Using pedometers to increase physical activity in overweight and obese women: a pilot study - Binns Colin; Egger Garry; Cheng Cheryl; Pal Sebely; Donovan Robert (BMC, 2009)
Abstract Background Most public health guidelines recommend that adults participate in 30 minutes of moderate intensity physical activity on most days of the week. Establishing new ways to achieve these targets in sedentary populations need to be explored. This research evaluated whether the daily use of pedometers could increase physical activity and improve health outcomes in sedentary overweight and obese women. Methods Twenty six overweight and obese middle-aged women were randomized into two groups: The control group was not able to record their steps daily, whilst the pedometer group, were asked to record the number of steps on a daily basis for 12 weeks. Results Our data showed that the pedometer group significantly increased their steps/day, by 36%, at the end of the 12 weeks, whereas the control group's physical activity levels remained unchanged. There was no significant difference in weight or body fat composition in the pedometer group compared to the control group. However, there was a significant decrease in systolic blood pressure in the pedometer group (112.8 ± 2.44 mm Hg) compared to the control group (117.3 ± 2.03 mm Hg) (p = 0.003). Conclusion In conclusion, this pilot study shows that the combination of having step goals and immediate feedback from using a pedometer was effective in increasing physical activity levels in sedentary overweight and obese women. Trial registration ACTRN12609000176268